Minimally Invasive Repair of Pectus Carinatum - ERMERAK, NEZİH ONUR; LAÇİN, TUNÇ (ELSEVIER SCIENCE INC, 2018)
Background. The second most common deformity of the anterior chest wall, pectus carinatum, is a diverse deformity that has been largely managed using open techniques. This study reviews clinical experience with a newly designed bar for minimally invasive repair of pectus carinatum. Methods. We reviewed the records of all patients recorded in our Chest Wall Deformities Clinical Database. Between January 2006 and November 2016, minimally invasive repair of pectus carinatum was performed in 172 patients. All met the criteria of a compression test of 10 to 25 kg/cm(2). The mean age was 17.3 years, and 22.7% had a positive family history of a congenital chest wall deformity. Symmetric and asymmetric deformities were treated. During our study period, we designed 4 different bar configurations and their related stabilizers. All patients are assessed every 3 to 6 months. After 2 to 3 years of follow-up, the bar and the stabilizers are removed. Results. Of 172 patients, 97.1% tolerated the procedure very well. The operation was a mean length 76.6 minutes. Average blood loss was 40 mL. Mean hospital length of stay was 3.7 days. Complications included pneumothorax, wire breakdown/rib cut, wound infection, severe pain, skin hyperpigmentation, nickel allergy, and overcorrection leading to excavatum. Patients returned to routine activity in 10 to 14 days. With a mean follow-up of 29.8 months in bar removal patients, 130 of 172 (93.8%) reported excellent results. Conclusions. Minimally invasive repair of pectus carinatum with the technically modified fourth-generation bar and its securing system has advantages of low morbidity, short hospital stay, and excellent cosmetic results, even in asymmetric cases. (C) 2018 by The Society of Thoracic Surgeons
Keywords: QUALITY-OF-LIFE; SURGICAL-CORRECTION; BODY-IMAGE; EXPERIENCE; MANAGEMENT; EXCAVATUM